PERAN PERPUSTAKAAN MASJID BAITURRAHMAN BALAI PANJANG SUMATERA BARAT DALAM TRADISI “KEMBALI KE SURAU” - Fadhila Nurul Husna Zalmi; Dian Hasfera; Arifah Yenni Gustia (Maktabatuna, 2019)
The library of the Baiturrahman Mosque in Balai Panjang, West Sumatra, is a place for the surrounding community to search for information and exchange information and learn in the fields of religion, social and culture. The collection is used to discuss and dialogue in sharing knowledge through several activities in "kembali ke surau" tradition in this mosque. Baiturrahman Mosque provides collections related to religious knowledge and Minangkabau customs, but in very limited quantities. This research uses the literature study method. Baiturrahman mosque library that already exist today visible only library functions as a venue. Where the mosque library is only used as a place for the transfer of knowledge in "kembali ke surau" tradition which was carried out at the Baiturrahman Mosque Balai Panjang West Sumatra.